Colloidal Force Study of Particle Fouling on Gas Capture Membrane. Issue 1 (December 2017) - Zhang, Lin; Hu, Bin; Song, Hang; Yang, Linjun; Ba, Long
Abstract Membrane fouling induced by industrial flue gas deteriorates their gas capturing efficiency, which is mainly caused by the adhesion of aerosol particles. To fully understand the mechanism of membrane fouling, a quantitative study of the adhesion force of particle on membrane surface was investigated by atomic force microscopy (AFM). The adhesion force of a single particle with flat glass, silicon wafer, PP (polypropylene) membrane, and fly-ash particles were measured within the relative humidity (RH) of 0 ~ 85%. The results showed the adhesion force of a particle with membrane have not much difference from the glass and silica wafer. And the surface roughness of flat substrate has slight effect on the adhesion force of the micrometer scale particle on flat surface at dry condition, while measured adhesion forces show obvious RH dependent for glass and membrane. Additionally, at dry conditions, the adhesion force of inter-particles also shows no obvious quantitative difference but obvious scattering comparing to that on membrane. The adhesion force of inter-particles increased more higher with the RH than that on membrane, which indicates the adhesion between micrometer scale particles can accelerate the deposition of particles on membrane and contributes the most to membrane fouling in industry atmosphere.